Optimization of Multigrain Beverage Formulas: The Effect of Cereals and Legumes on Physical Characteristics - Mulyaningtias, Irena Dwi; Faridah, Didah Nur; Muhandri, Tjahja (Indonesian Journal of Applied Research (IJAR), 2026)
Multigrain beverages were ready-to-drink products that were easy to consume at any time and contained high levels of soluble fiber, vegetable protein, unsaturated fatty acids, vitamin B complex, and phenolic compounds. Multigrain beverages were generally made from cereals and nuts. One problem associated with multigrain drinks was sedimentation and phase separation. The stability of the resulting drink depended on the type of raw material used. Therefore, this study aimed to optimize the processing of the physical characteristics of multigrain drinks. This study used Response Surface Methodology (RSM) with a D-optimal mixture design involving concentration factors of sweet corn (10–20%), red beans (20–30%), green beans (15–25%), black rice (10–20%), and sorghum (15–25%). The physical characteristics analyzed included viscosity, turbidity, suspension stability, and total solids. The results showed that a composition consisting of sweet corn at 19.75%, red beans at 20%, green beans at 25%, black rice at 10.25%, and sorghum at 25% yielded a desirability value of 0.816, with a viscosity of 63.4 mPa·s, turbidity of 115.4 ntu, suspension stability of 0.86%, and total solids of 9.11%, providing the optimum formula for producing high-quality multigrain drinks with high physical stability.